Advanced Paternal Age and Parental History of Schizophrenia - Miller, Brian (Schizophr Res, 2011)
INTRODUCTION: Advanced paternal age (APA) is a risk factor for nonaffective psychosis (NAP) in the offspring, although the mechanism(s) of this association are not clear. The aim of this study was to examine whether later childbearing can be explained by parental schizophrenia, and in doing so, further evaluate the “de novo mutation” hypothesis for the association between APA and NAP. METHODS: Using binary logistic regression, the association between APA and parental history of schizophrenia in the offspring, considering maternal and paternal history separately, was examined in 1) all persons with NAP born in Finland between 1950 and 1969 (Finnish NAP Cohort, n=13,712), and 2) members of the Northern Finland 1966 Birth Cohort (NFBC 1966, n=10,224), a general population birth cohort. RESULTS: In the Finnish NAP Cohort, having a mother with schizophrenia was associated with APA (Odds Ratio [OR] for linear trend=1.20, 95% confidence interval 1.12–1.29, p<0.01). In the NFBC 1966 sample, having a mother with schizophrenia was associated with APA at the trend level (OR=1.14, 0.99–1.31, p=0.07). By contrast, there was no association between having a father with schizophrenia and APA. DISCUSSION: In both a general population cohort and a birth cohort of subjects with nonaffective psychosis, APA was associated with maternal, but not paternal, schizophrenia. These findings suggest that increased genetic risk from the mother may explain the association between APA and nonaffective psychosis, and argue against the “de novo mutation” hypothesis.